Learning with multiple representations - Someren, Maarten W. van (Advances in learning and instruction series., 1998)
"When knowledge in a domain serves different tasks, such as diagnostic problem solving in medicine and explaining/communicating this knowledge to others, knowledge representation and handling pose difficult problems."--BOOK JACKET. "This book provides answers to questions of multiple representations in human reasoning and learning. Computational approaches to learning with multiple representations are introduced and discussed. Finally, the role of multiple representations in teaching is addressed."--BOOK JACKET. "Learning with Multiple Representations is one of the outcomes of the European Science Foundation's research programme on "Learning in Humans and Machines", and will be of interest to a wide audience of psychologists, computer scientists and educational scientists."--Jacket